HUBUNGAN PENGGUNAAN MUKTIMEDIA INTERAKTIF BERBASIS POWERPOINT DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMP NEGERI 15 MAKASSAR - Pratiwi, Nur Hikmah; Mustamin; Raehana, Syarifa; Syahid, Akhmad; Azhar, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the use of PowerPoint-based interactive multimedia in learning Islamic Religious Education, the level of students' interest in learning, and the relationship between the two. This study uses a quantitative approach with a correlational type. The research population was all students of grade VIII of SMP Negeri 15 Makassar, with a sample of 72 students. The data collection technique uses questionnaires, observations, and documentation, while data analysis uses Product Moment correlation. The results showed that the use of PowerPoint-based interactive multimedia was in the good category with an average score of "36.61", and the students' learning interest was also in the good category with an average score of "36.75". In addition, that ,r-calcul.=0.613 which is in the interval of 0.60-0.799 is greater than the value of ,r-table.=0.232 at a significance level of 5%. Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, there is a significant (strong) relationship between the use of PowerPoint-based interactive multimedia and students' learning interests in PAI subjects grade VIII at SMP Negeri 15 Makassar.